Talent Mapping Process in Improving Employee Performance at PT Sinergi Visi Utama - Daniswara Alif Anargya Nugroho; Fereshti Nurdiana Dihan (PT SOLUSI EDUKASI BERDIKARI, 2024)
PT Sinergi Visi Utama does not yet have a mature and structured talent mapping system or process. Talent mapping is an important early stage in determining the success of the human resource development process in talent management. Through talent mapping, companies can identify, evaluate, and select individuals to be placed in positions that match their respective skills and potential. This research uses a qualitative approach because it focuses on the talent mapping process at PT Sinergi Visi Utama. Currently, the company only implements employee development through formal education, such as sending employees to S2 and S3 levels, without a more in-depth overall strategy. Providing further education has proven to have a positive impact on employee motivation, innovation, and overall performance. Therefore, a more systematic and planned implementation of talent mapping is needed to identify and develop employee potential optimally.